The Physical Chemistry of the Enigmatic Phospholipid Diacylglycerol Pyrophosphate - Strawn, Liza; Babb, Amy; Testerink, Christa; Kooijman, Edgar E. (Frontiers in Plant Science, 2012)
Phosphatidic acid (PA) is a lipid second messenger that is formed transiently in plants in response to different stress conditions, and plays a role in recruiting protein targets, ultimately enabling an adequate response. Intriguingly, this increase in PA concentration in plants is generally followed by an increase in the phospholipid diacylglycerolpyrophosphate (DGPP), via turnover of PA. Although DGPP has been shown to induce stress-related responses in plants, it is unclear to date what its molecular function is and how it exerts its effect. Here, we describe the physicochemical properties, i.e. effective molecular shape and charge, of DGPP. We find that unlike PA, which imparts a negative curvature stress to a (phospho)lipid bilayer, DGPP stabilizes the bilayer phase of phosphatidylethanolamine (PE), similar to the effect of phosphatidylcholine (PC). DGPP thus has zero curvature. The pKa2 of the phosphomonoester of DGPP is 7.44 ± 0.02 in a PC bilayer, compared to a pKa2 of 7.9 for PA. Replacement of half of the PC with PE decreases the pKa2 of DGPP to 6.71 ± 0.02, similar to the behavior previously described for PA and summarized in the electrostatic-hydrogen bond switch model. Implications for the potential function of DGPP in biomembranes are discussed.